1995
DOI: 10.1161/01.cir.92.5.1274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Left Ventricular Hypertrophy Secondary to Chronic Pressure Overload on Transmural Myocardial 2-Deoxyglucose Uptake

Abstract: The pressure-overloaded hypertrophied left ventricle demonstrated increased accumulation of 2DGP detected with 31P NMR spectroscopy. Accumulation of 2DGP was positively correlated with the degree of hypertrophy and was most marked in the subendocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 35 publications
5
42
0
1
Order By: Relevance
“…In hearts with cardiac hypertrophy, we have previously reported that myocardial PCr/ATP is significantly decreased, which is linearly related to the severity of hypertrophy and LV dysfunction and is independent from a persistent myocardial ischemia (35)(36)(37)39). These LVH hearts are also associated with a significant lower myocardial total creatine level (36 -39), which, in principle, can cause the reduction of the myocardial creatine phosphate level.…”
Section: Discussionmentioning
confidence: 94%
“…In hearts with cardiac hypertrophy, we have previously reported that myocardial PCr/ATP is significantly decreased, which is linearly related to the severity of hypertrophy and LV dysfunction and is independent from a persistent myocardial ischemia (35)(36)(37)39). These LVH hearts are also associated with a significant lower myocardial total creatine level (36 -39), which, in principle, can cause the reduction of the myocardial creatine phosphate level.…”
Section: Discussionmentioning
confidence: 94%
“…One of the primary functions of AMPK activation is to induce glucose uptake, which has been observed in hypertrophied hearts of animal models ( 165 ) and humans ( 166 ), suggesting a functional role of AMPK in cardiac hypertrophy ( 162,167 ) and ischemia ( 168,169 ). Further evidence of AMPK in cardiac function comes from AMPK mutation that leads to myocardial metabolic storage disease with coexistence of hypertrophy and defects in conduction system ( 167 ).…”
Section: Role Of Ampk In Cardiac Functionmentioning
confidence: 99%
“…50 It is now widely accepted that glucose uptake and utilization increase in hypertrophied and mildly failing heart. [51][52][53][54] It is not yet clear how long this is sustained.…”
Section: On the Failure Of Atp Synthesis Pathways To Prevent The Decrmentioning
confidence: 99%